Brand Experience: A Review of 39 Years of Research Development - Moh. Darus Salam (TIJAB (The International Journal of Applied Business), 2020)
This study explored the trends of academic research on brand experience using bibliometric methods. The exploration included statistical data from published articles on Scopus database. Relevant articles were extracted from Scopus indexed journals using keywords collected through online survey. The analysis covered 1,920 articles in 484 journals published between 1981 and 2020. This study recognized prominent scholars, institutions, sources as well as the most cited articles of brand experience research. Some important and most used keywords in brand experience publications were also identified. Study findings indicated growing interest in brand experience research despite publication absence in some of the early years of its development. The most cited article was written by Fournier in 1998 entitled “Consumers and Their Brands: Developing Relationship Theory in Consumer Research.” Journal of Business Research was the most cited journal in the area with 5,010 citations and has become the most productive journal with 83 titles.